2021
DOI: 10.1007/s00204-021-03141-w
|View full text |Cite
|
Sign up to set email alerts
|

The human hepatocyte TXG-MAPr: gene co-expression network modules to support mechanism-based risk assessment

Abstract: Mechanism-based risk assessment is urged to advance and fully permeate into current safety assessment practices, possibly at early phases of drug safety testing. Toxicogenomics is a promising source of mechanisms-revealing data, but interpretative analysis tools specific for the testing systems (e.g. hepatocytes) are lacking. In this study, we present the TXG-MAPr webtool (available at https://txg-mapr.eu/WGCNA_PHH/TGGATEs_PHH/), an R-Shiny-based implementation of weighted gene co-expression network analysis (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(64 citation statements)
references
References 78 publications
(111 reference statements)
2
62
0
Order By: Relevance
“…A design classifier specifying the combination of compound, concentration and timepoint was used as design formula in the DESeq-DataSet object. DESeq2 results, performed separately for PHH and HepG2 samples, were extracted per design classifier using the result function with alpha = 0.05, and uploaded to the PHH TXG-MAPr [41]. This method arranges genes in predefined modules of co-regulated genes and calculates eigengene scores (EGSs) for modules that represent their (de)activation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A design classifier specifying the combination of compound, concentration and timepoint was used as design formula in the DESeq-DataSet object. DESeq2 results, performed separately for PHH and HepG2 samples, were extracted per design classifier using the result function with alpha = 0.05, and uploaded to the PHH TXG-MAPr [41]. This method arranges genes in predefined modules of co-regulated genes and calculates eigengene scores (EGSs) for modules that represent their (de)activation.…”
Section: Methodsmentioning
confidence: 99%
“…We evaluated gene expression profiles by TempO-Seq analysis in combination with the targeted S1500+ gene set [36] for PHH samples derived from 50 donors and for HepG2 cells exposed to cisplatin (S1C Fig) . Dimensionality reduction based on the normalized expression of all genes in the transcriptomics data set neither revealed outlying donors nor clearly distinguishable subgroups of donor samples, except for the HepG2 cells that had clearly different gene expression patterns (S1D Fig) . We further explored the similarity in differential gene expression profiles of HepG2 cells and PHHs in response to cisplatin-induced DNA damage by comparing the activated genes based on PHH TXG-MAPr gene sets termed 'modules' [41]. Modules 83, 59 and 391, associated to p53 signaling and DNA damage, were among the twenty modules with the highest eigengene scores in HepG2 cells or PHHs exposed for 8 or 24 hours to 3.3 μM cisplatin (S1E Fig) and in the top 20 activated modules in response to the DNA damaging compound etoposide in the PHH TXG-MAPr.…”
Section: Dna Damage-related Gene Activation Upon Cisplatin Treatment ...mentioning
confidence: 99%
“…Gene sets are derived to predict for genotoxicity and receptor-mediated toxicity. For example, the use of toxicogenomics-MAPr (TXG-MAPr, , accessed on 10 December 2021) to build such predictive biomarkers, applied to hepatocarcinogens in rodent models and clinical studies for pharmaceuticals, looks promising, as reported in two recent independent studies [ 39 , 40 ]. Corton et al determined six common MIEs in rodent liver cancer adverse outcome pathways (AOPs) using short-term in vivo assays, for the early identification of carcinogenic potential.…”
Section: Transcriptomic Assays and Gene Panels To Identify Key Cell S...mentioning
confidence: 99%
“…Interestingly, Callegaro et al further developed the application of the TXG-MAPr model web tool (available at , accessed on 9 November 2021), that weights gene co-expression networks (WGCNA) obtained from the Primary Human Hepatocytes (PHH) TG-GATEs dataset [ 40 ]. On the basis of analyses of 50 different PHH donors’ responses to a common stressor, tunicamycin, the authors constructed module associations using donors pre-existing disease states/variability.…”
Section: Transcriptomic Assays and Gene Panels To Identify Key Cell S...mentioning
confidence: 99%
“…This platform was established by a data-driven weighted gene co-expression network analysis (WGCNA) based on a large TG-GATEs rat transcriptomics dataset from rat kidney after nephrotoxicant treatment with different doses and time points 9 . The DIKI-TXG-MAPr facilitates analysis of renal pathology-relevant co-expressed gene networks (modules) enriched for specific biological responses and transcription factor target genes that provide biological interpretation based on module induction or repression 19,20 . Induction or repression of each module, and by analog the associated biological processes annotated for that module, is quantified using a single eigengene score (EGs) based on the fold-change expression of individual gene network memberships 21 .…”
Section: Introductionmentioning
confidence: 99%